Concurrent Hairy Cell Leukemia and Metastatic Merkel Cell Carcinoma - Ajay Prakash; Alhossain A. Khalafallah (Case Reports in Oncological Medicine)
Hairy cell leukemia (HCL) and Merkel cell carcinoma (MCC) are two rare malignancies with distinct cells of origin. HCL is a lymphoid malignancy of mature B cells, and MCC derives from neuroendocrine cell origin. HCL has a favorable prognosis with most patients achieving long-term remission and potential cure. In contrast, MCC is an aggressive malignancy affecting the skin and can metastasize quickly with a dismal prognosis. Immunocompromised patients, such as those with AIDS, posttransplant, and the elderly, have higher incidences than the general population, suggesting a possible immune mechanism. We report a case where a patient presented with HCL and metastatic MCC synchronously. This is the first reported case of these two rare malignancies occurring concurrently at initial presentation and may represent a role of immunosuppression in the pathogenesis of MCC.